When Molecular-Targeted Agents Meet Immunotherapy: The Opportunities for Soft Tissue Sarcoma - Vanina E. Wainsztein; Tom W. Chen (Journal of Immunotherapy and Precision Oncology, 2020)
Soft tissue sarcomas (STS) account for less than 1% of adult cancers with a median overall survival of 12 months in the metastatic setting. Although chemotherapy remains the standard of treatment for advanced disease, molecular targeted agents (MTAs) and immunotherapies are under intensive investigation in STS. The success of MTAs comes mainly from antiangiogenic agents in various STS subtypes, from colony-stimulating factor-1 receptor inhibitor in tenosynovial giant cell tumor and neurotrophic tropomyocin receptor kinase (NTRK) inhibitors while others, such as cyclin-dependent kinase (CDK)-4 inhibitors, remain under evaluation. In advanced STS the activity of single-agent immunotherapy was not paradigm-changing as in other tumor types. A better understanding of tumor microenvironment, the immunogenic properties of MTAs, and finding an optimal treatment combination to improve patients outcomes became a central topic of research and discussion. Furthermore, the development and incorporation of transcriptomic profiling-based classification will allow identification, refined patient selection, and guided-treatment assignment. This article reviewed recent advances in STS treatment in MTAs and immunotherapy, strategies to overcome resistance, and outcomes of combination treatments in different STS subtypes. Promising preliminary results from combination strategies have shed light on STS treatment. The increasing understanding of this heterogeneous group of tumors and its microenvironment biology may help develop and guide treatment strategies with MTA and immunotherapies, alone or in combination, in a tailored way based on predictive and validated biomarkers and tumor molecular profiling in this new coming era.